(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
This paper aims toreviewthe importance ofsmall and medium projectsin achievingeconomic and social development. This result of this study will help to identify the success factors required to finance small and medium projects by Islamic Banks. The study defined the Islamic banks and the principles of small and medium projects in the economies of some countries. In addition to that the study discussed the classification of these projects according to the criteria of employment rate based on economic development, also identifying the nature of these projects and selection criteria. Finally the study discussed the principles of Islamic finance and its main goals, selection standards and criteria to small and medium projects, and the Islamic finance techniques used by Islamic banks to finance these projects.